The effect of chlorine dioxide on Enterococcus faecalis in exponential, stationary and starvation phases in extracted human teeth - an invitro study - Somayaji, Krishnaraj; KL, Shoba; Rao, Mohandas (International Journal of Medicine, 2014)
Background: Enterococcus Faecalis (E faecalis) is isolated usually from failed root canal treated teeth. It can bind to dentin and co-aggregate with other organisms. The organism is resistant to the intracanal medicaments and irrigants. It has the ability to produce biofilms and survive within the root canal. They may develop resistance at different phases of bacterial growth cycle. Objective: To study the effect of chlorine dioxide on different phases of E faecalis growth cycle for 1 and 3 min duration. Methodology: E faecalis ATCC strain (29212) was cultured in different growth phases on dentinal blocks of extracted human teeth. After treatment with chlorine dioxide, left out colonies were counted from dentinal shavings. Observation of the remaining biofilm of different phases was made using the scanning electron microscope and comparison between them was done. Results: In all 3 phases, at the end of 1 and 3 min, significantly (p